Some effects of gamma-irradiated autologous sera on their donors - Rossetini, S. M O; Levanon, Y. (My University, 1977)
The present paper is a further step to elucidate the effect of γ-irradiated molecules and their action as immunogens. Rabbits were bled, the total serum was γ-irradiated and reinjected to the autologous donor. Bleeding and reinjection of non-irradiated serum do not produce any alteration hence the animal is able to recognize the autologous unmodified serum proteins as 'self'. Electrophoretic results demonstrate that as an effect of γ-irradiation, alteration of the normal migration properties are occurring. The obtained data are suggesting that due to the possible alteration of the molecular structure, resulting as the effect of γ-rays, the antibody forming system of the animal injected with irradiated autologous serum might recognize the substances as 'not self' what may be the possible reason of antibody formation. The presence of antibodies and probably their complexes with antigens are demonstrated by cutaneous sensibilization technics. The low level of the complement starting from the 7-9 days, the histological alteration of the kidney and the cardiac lesions are tempting to try an interpretation comparing these symptoms to those observed in serum sickness.
Keywords: antigen; animal experiment; gamma radiation; serum